The cult of King Charles the martyr - Lacey, Andrew, 1960- (Woodbridge, Suffolk ; Rochester, NY : Boydell Press, 2003)
The first study to deal exclusively with the cult ofKing Charles the Martyr - Charles I as suffering, innocent king, walking in the footsteps of his Saviour to his own Calvary at Whitehall - and the political theology underpinning it, taking the story up to 1859.
The royal actor -- Habeas corpus : foundations of the cult before 1649 -- By the rivers of Babylon : the cult in exile -- In verbo tuo spes mea : fashioning the royal martyr -- The return to Zion : he cult and the restored monarchy -- Irreligious rants and civil seditions : the cult in 'the age of party' -- A pattern of religion and virtue : the conservative martyr -- Our own, our royal saint.
Includes bibliographical references (pages 252-302) and index.
Print version record.
JSTOR
Keywords: Charles -- I, -- King of England, -- 1600-1649 -- Cult; Church of England; Charles -- I, -- King of England, -- 1600-1649; Book of common prayer (Church of England); Christian martyrs -- Great Britain -- Biography; Christian saints -- Great Britain -- Biography; Great Britain -- Kings and rulers -- Biography; Martyrs chrétiens -- Grande-Bretagne -- Biographies; RELIGION -- Christianity -- Anglican; HISTORY -- Modern -- General; Christian martyrs; Christian saints; Cults; Kings and rulers; Great Britain; Biographies; Biographies; Biographies